Recombinant Mycoplasma mycoides proteins elicit protective immune responses against contagious bovine pleuropneumonia - Nkando, I.; Pérez Casal, J.; Mwirigi, M.; Prysliak, T.; Townsend, H.; Berberov, E.; Kuria, J.; Mugambi, J.; Soi, R.; Liljander, Anne M.; Jores, Joerg; Gerdts, V.; et al. (Elsevier, 2016)
Mycoplasma mycoides subsp. mycoides (Mmm) is the causative agent of contagious bovine pleuropneumonia (CBPP), a devastating respiratory disease mainly affecting cattle in sub-Saharan Africa. The current vaccines are based on live-attenuated Mmmstrains and present problems with temperature stability, duration of immunity and adverse reactions, thus new vaccines are needed to overcome these issues. We used a reverse vaccinology approach to identify 66 Mmm potential vaccine candidates. The selection and grouping of the antigens was based on the presence of specific antibodies in sera from CBPP-positive animals. The antigens were used to immunize male Boran cattle (Bos indicus) followed by a challenge with the Mmm strain Afadé. Two of the groups immunized with five proteins each showed protection after the Mmm challenge (Groups A and C; P < 0.05) and in one group (Group C) Mmm could not be cultured from lung specimens. A third group (Group N) showed a reduced number of animals with lesions and the cultures for Mmm were also negative. While immunization with some of the antigens conferred protection, others may have increased immune-related pathology. This is the first report that Mmm recombinant proteins have been successfully used to formulate a prototype vaccine and these results pave the way for the development of a novel commercial vaccine.